Роман со вкусом капучино: повесть / Анна Антонова - Антонова Анна (Только для девчонок, 2010)
Экземпляры: ф.23 (20250224) / Инвентарный номер: 65632 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: А 72 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44